The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1109/tap.2008.927566
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Validation for the Incremental Theory of Diffraction

Abstract: Experimental and theoretical approaches to verify the\ud validity of the incremental theory of diffraction (ITD) are considered.\ud After providing a simple recipe for the application of the ITD,\ud three geometries are examined for its validation. First, the ITD formulation\ud of the diffraction from a perfect electric conductor (PEC)\ud straight wedge is compared with the uniform theory of diffraction\ud (UTD) and with measurement results. Second, the ITD formulation\ud of the diffraction from a PEC disc is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
1
2
0
3
Order By: Relevance
“…The asymptotic analysis performed here yields high‐frequency, closed form expressions which explicitly satisfy reciprocity, and are well behaved at any incident and observation aspects, including those close to and at the longitudinal coordinate axis of the cylindrical configuration. An analytical verification for the case of a disk is provided by Erricolo et al [2007]. It is also found that, for the scalar case, the same result was obtained by Rubinowicz [1965], by means of an entirely different method.…”
Section: Introductionsupporting
confidence: 68%
“…The asymptotic analysis performed here yields high‐frequency, closed form expressions which explicitly satisfy reciprocity, and are well behaved at any incident and observation aspects, including those close to and at the longitudinal coordinate axis of the cylindrical configuration. An analytical verification for the case of a disk is provided by Erricolo et al [2007]. It is also found that, for the scalar case, the same result was obtained by Rubinowicz [1965], by means of an entirely different method.…”
Section: Introductionsupporting
confidence: 68%
“…This behavior is due to the rapid spatial variation and to the non ray-optical behavior of the field diffracted by the first edge when it illuminates the second wedge. The same limitation is expected to affect the ITD representation [18], [19], [21], [35], thus preventing a simple cascaded application of the ITD coefficients for single diffraction. Therefore, it is necessary to develop an ITD double-diffraction coefficient that uniformly accounts for the different transitions that may occur.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the scattering by wedges may also be computed with the Incremental Theory of Diffraction (ITD) [6]- [9] and the ITD was recently extended in [10] to compute CSP diffraction by metallic objects. The ITD is considered because, in many cases, it overcomes the typical impairments of the GTD/UTD ray techniques associated with possible ray caustics and with the difficulties of ray tracing in complex space.…”
Section: Introductionmentioning
confidence: 99%